A Case Report on Tibial Plateau Fracture Fixed with Combination of Hybrid and Knee Spanning Fixator in Gustilo-Anderson Type 3b Injury - Uday Raman,; Hardika Mangal, (Indian Journal of Case Reports, 2021)
Tibial plateau fractures involve the intra-articular portion of the proximal tibia with or without metaphyseal extension. Here, we present the case of a 25-year-old male patient presented with Schatzker type 6 tibial plateau fracture associated with a lateral femoral condyle fracture and a vertical patella fracture fixed with a combination of hybrid ring fixator, cannulated cancellous screws, and a knee spanning frame in Gustilo-Anderson type 3 B injury. The purpose of this case report is to highlight the surgical challenges faced in such types of cases that include the Gustilo and Anderson type 3 B injury with complicated fracture morphology, the implant to be used with his current economic status, and the limited investigations available.